2020
DOI: 10.1186/s12886-020-01466-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment optical coherence tomography imaging in peripheral ulcerative keratitis, a corneal structural description

Abstract: Background: Anterior segment optical coherence tomography (AS OCT) is a helpful tool used to diagnose and manage many corneal conditions, but its use has not been reported in case of peripheral ulcerative keratitis (PUK). The aim of this study is to describe AS OCT findings in cases of PUK. Methods: Retrospective observational case series of six eyes presenting with a PUK and proven systemic vasculitis. Clinical course, slit lamp photographs, and AS OCT findings were the main outcomes. Results: The AS OCT find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Identification of the basement membrane line serves as an important diagnostic criterion since its involvement in the pathological process affects the outcome of corneal trauma [9]. The next layer of the cornea is the stroma, which has a homogeneous and uniform structure across its entire plane, thanks to the content and arrangement of type 1 collagen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the basement membrane line serves as an important diagnostic criterion since its involvement in the pathological process affects the outcome of corneal trauma [9]. The next layer of the cornea is the stroma, which has a homogeneous and uniform structure across its entire plane, thanks to the content and arrangement of type 1 collagen.…”
Section: Resultsmentioning
confidence: 99%
“…AS-OCT provides high-resolution, in vivo cross-sectional images of the cornea and anterior chamber of the eye, corresponding to the histological structure of the corneal tissue. It allows for the assessment of morphological and structural changes in various layers of the cornea in cases of trauma, inflammatory processes, and dystrophic changes, as well as after ophthalmic surgeries [9,10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated the usefulness of the AS-OCT in the clinical evaluation of a large number of corneal pathologies and in assessing the differences between normal and abnormal epithelium in the ocular surface neoplasia [ 29 , 30 , 31 ]. The undisputed role of AS-OCT in corneal assessment was reported in cases of edema, corneal infiltrates in microbial keratitis, and in peripheral ulcers [ 9 , 10 , 11 , 12 , 22 ]. AS-OCT also became a fundamental tool in the study of stromal deposits and structural changes in corneal dystrophies and degenerations and in the evaluation of the progression of keratoconus [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also crucial in corneal lamellar surgery and in the study of ectatic pathologies, and a proven utility in the evaluation of pterygium, pinguecula, and scleromalacia [ 2 , 4 , 5 , 6 , 7 , 8 ]. Different studies have highlighted the role of AS-OCT in the management of corneal infections such as keratitis and peripheral ulcers [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the inflammation intensity declines, irregular hyporeflective epithelium, a smoother anterior stroma, and a homogeneous hyperreflective stroma can be seen. On the other hand, healed PUK lesion is characterized by a filled corneal defect with a hyporeflective thick epithelium, a demarcation line, and the persistence of the hyperreflective underlying stroma [35,36].…”
Section: Clinical Presentationmentioning
confidence: 99%